Application and Interpretation of High-resolution Manometry for Pharyngeal Dysphagia - Ryu, Ju Seok; Park, Donghwi; Kang, Jin Young (Journal of neurogastroenterology and motility, 2015)
The pharyngeal phase of swallowing is a complex event consisted with subsequent muscular contractions and pressure gen-eration to move a bolus from the mouth to the esophagus. Recently, high-resolution impedance manometry (HRIM) was devel-oped and used for the evaluation of pharyngeal dysphagia. Although HRIM provides precise pharyngeal pressure information, it has yet to be used as part of routine clinical practice for the assessment of dysphagia. The main reasons are thought to be that the test method and result interpretation are not easily applicable and standardized. The anatomical landmarks for HRIM parameters are velopharynx, tongue base, epiglottis, low pharynx, and upper esophageal sphincter. With HRIM, the pressure and timing data could be obtained at a precise anatomical structure. In the present review, we will review how to apply HRIM for the evaluation of pharyngeal dysphagia, including the interpretation of its parameters.(J Neurogastroenterol Motil 2015;21:283-287).